English as a lingua franca in tourism: A case-based analysis of communication breakdowns and service recovery in tourist encounters - Kurniawan, Taufiq; Agust, Satria; Arum Sari, Valentina Dyah; Lestari, Titi; Latuni, Glenie (Journal of International Students, 2026)
English as a Lingua Franca (ELF) plays a vital role in global tourism, facilitating communication between international tourists and service providers but often causing miscommunication due to differing proficiencies, accents, and cultural norms. Such breakdowns can lead to service failures, underscoring the need for effective recovery. This qualitative case study explores ELF interactions in hotels, restaurants, travel agencies and tour operations across three destinations in Lombok, Indonesia. Data from observations, recordings, interviews and complaint documents were analysed using discourse and thematic methods. Four main breakdowns emerged: lexical misunderstandings, pronunciation issues, pragmatic failures and cultural mismatches, where lexical and pragmatic being most frequent. Recovery strategies included clarification, apology, non-verbal support, compensation and proactive adjustment, with cultural expectations mediating success. Relational and proactive approaches yielded the greatest satisfaction. The study integrates ELF service recovery theory, highlighting practical training in cross-cultural pragmatics and flexible recovery to improve multilingual service quality.